Management of Rectal Prolapse in Children as a Day Care Procedure - Rahman, SM; Hasanuzzaman, ASM; Huda, SMS (Journal of Dhaka Medical College, 2010)
Rectal prolapse is a relatively common self limiting problem in young children. The peak age of prolapse is 2-3 years, a time during which the rectal mucosa is relatively loosely adherent to the underlying muscles, pelvic floor musculature is not fully developed and sacrum is relatively flat which directs increases in intra abdominal pressure towards anus instead of the protected hollow of the pelvi’s1,2. Rectal prolapse is a very common childhood problem in our country due to frequency of diarrhoeal and parasitic diseases accentuated by lack of personal hygiene and mal-nutrition, Majority of the patients are poor; majority of childhood prolapse are mucosal limited to 2-3 cm from anal verge 3. Diagnosis of rectal prolapse is straight forward by inspection and palpation. Colonoscopy and Barium enema are indicated only to exclude any other secondary causes in suspected cases. We have managed 30 (thirty) cases of recurrent rectal prolapse after failure of medical treatment in a prospective study by injection sclerotherapy as a Day care procedure; 5% phenol in olive oil was used as sclerosing agent and the procedure was performed under general anaesthesia and caudal block. The patients were kept under observation for 4-6 hours. 28 (twenty eight) patients responded satisfactorily (93.3%); 2 patients (6.67%) needed open operation -rectopexy. Only one patient was admitted for 48 hours due to reactionary haemorrhage which was managed conservatively. Few patients had minor complications like constipation, diarrhoea and acute retention; all managed conservatively. There was no mortality. Injection sclerotherapy appeared to be a safe, effective and cheap procedure for management of rectal prolapse in children. DOI: 10.3329/jdmc.v17i2.6594 J Dhaka Med Coll. 2008; 17(2) : 116-120